PENILAIAN RISIKO TERHADAP PERLUASAN PENDAPATAN NON-BUNGA PERBANKAN DI INDONESIA - Desta Rizky Kusuma (Universitas Ahmad Dahlan, 2015)
Growth in non-interest income in excess of interest income on banks in Indonesiabecame the motivation and background in this research. The condition is one of thebank’s efforts to stabilize revenue, or referred to diversify income. Research in thefi eld of bank income diversifi cation, especially in the developed countries give mixedresults and contradictory, while in Indonesia is still relatively little is reviewing thisphenomenon. Aims of the study, the fi rst to test the effect of non-interest income of thebank’s accounting and market risk. Second, examine the effect of non-interest incomefrom fee based on accounting and market risk. The object of research is banking inIndonesia, with a sample of banks listed on the Indonesia Stock Exchange (BEI) fromthe year 2010 to 2012. The research data were mostly obtained from the Stock Exchangeand the Bank of Indonesia Banking Directory (DPI). Non-interest income is proxied bytwo variables: net non-interest income and fee-based revenue. Risk is measured onthe basis of accounting and the market, the risk is proxied by the variable accountingstandard deviation of ROA, while the market risk variable is proxied by the standarddeviation of stock returns.